As associações capitalistas eborenses : actores, áreas de negócio e ritmos de formação (1889-1960) - Guimarães, Paulo Eduardo (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Departing from the analysis of the commercial and industrial register, this article describes the emerging business areas in the area of Évora and the social actors involved in them, considering the legal types assumed by the capital associations, as well as their evolution through the period occurred between 1889 and 1960. One argues that the associations performed different “functions”, being a means for launching a new activity, involving creditors of pre-existing singular companies or guaranteeing the transfer of business. In this process, the elites participated in the constitution of wider societies, connected with banking, insurances, or the trade and processing of raw materials originating from the great capitalist agricultural exploitation. The analysis of the commercial register has revealed the regional business networks with connections to the capital and the world economy, involving owners, farmers, tradesmen and industrialists.